Governance, institutional stewardship and local identity: the Area Regional Territorial Plans experience in Lombardy (Ciudades, 2020)
This paper analyses the planning implementation conducted by the Lombardy Region, in two different inter-municipal realities, as a useful example in a local context: the Area Regional Territorial Plan Alpine Valleys and the Area Regional Territorial Plan of the Franciacorta geographical area. These two complex experiences suggest positive conditions for the implementation of policies of Urban-Rural/Mountain partnerships to reach common goals and enhance urban-rural relationships, and complex institutional/administrative frameworks for activating multi-level governance processes.
Keywords: Territorial planning; urban-rural relationship; multilevel governance; inter-municipal cooperation tools; Lombardy Region